A case report of transmission and disease caused by Mycobacterium caprae and Mycobacterium bovis in Lima, Peru - Amber Shrestha; Janeth Picoy; Arturo Torres; David A. Moore; Robert H. Gilman; Jorge Coronel; Louis Grandjean (BMC Infectious Diseases, 2021)
Abstract Background The Tuberculosis (TB) burden in Peru is significant with respect to both disease morbidity and mortality. Furthermore the recent diversification of farming enterprise to include a wide range of animal species has necessitated the consideration of members of the Mycobacterium Tuberculosis Complex (MTBC) with the potential for zoonotic transmission. M. bovis and M. caprae, a lesser known member of the MTBC exhibit an exceptionally wide host spectrum in animals and are capable of causing disease in humans. M. bovis has a predictable resistance profile which includes resistance to pyrazinamide. Thus, failure to identify M. bovis as the causative agent in reported TB cases leads to higher levels of treatment failure and contributes to the transmission of drug-resistant TB. Case presentation Reported here are the clinical presentations, investigations and treatment histories of two patients identified from a population level genotyping study in Lima, Peru that were at the time of treatment thought to be M. tuberculosis patients but in retrospect were spectated using whole genome sequencing as M. caprae and M. Bovis. Conclusions The cases reported here constitute convincing evidence that M. caprae and M. bovis are causative agents of TB infection in humans in Peru and underscore the importance of species-level MTBC member identification to effectively control and treat zoonotic TB. Furthermore these cases highlight the challenges of using clinical risk factors to identify cases of zoonotic TB in humans as their clinical presentation and transmission history is often difficult to distinguish from anthroponotic TB.